CEFR AS A GUIDING FRAMEWORK: ENHANCING ENGLISH PROFICIENCY AMONG MALAYSIAN KINDERGARTEN CHILDREN - Azlan Abdul Rahman; Sharina Saad; Razanawati Nordin; Chuah Bee Peng; Syahrini Shawalludin (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The increasing global demand for English proficiency has positioned early childhood education as a critical juncture for language acquisition, particularly in Malaysia, where English serves as a second language (ESL) and plays a pivotal role in education and economic development. However, despite ongoing efforts to improve English language teaching, significant challenges persist, particularly in aligning pedagogical practices with internationally recognized frameworks such as the Common European Framework of Reference for Languages (CEFR). While the CEFR has been widely implemented at primary, secondary, and tertiary levels in Malaysia, its application in kindergarten settings remains underexplored, leaving a critical gap in early childhood education. This conceptual paper aims to propose a theoretical framework that aligns CEFR principles with the unique demands of English language teaching among Malaysian kindergarten children. A comprehensive review of existing literature highlights the need for developmentally appropriate approaches, culturally responsive pedagogies, and enhanced teacher training to address disparities in resource availability and multilingual contexts. The proposed framework integrates CEFR’s Pre-A1 level descriptors, communicative competence, and task-based language teaching with play-based learning environments ensuring alignment with both global benchmarks and local needs. Key findings suggest that adapting CEFR principles for kindergarten education can significantly enhance English proficiency while fostering cognitive, social, and academic development. The implications of this study extend to policymakers, educators, and researchers, emphasizing the importance of age-specific guidelines, professional development programs, and cross-disciplinary collaboration. By addressing these gaps, this paper contributes to the broader discourse on early language acquisition and provides a roadmap for enhancing English proficiency among Malaysian kindergarteners. Further research is needed to empirically validate the proposed framework and explore its long-term impact on children’s language development and global readiness.